Japanese Character Education Through Anime as Across Culture in Makassar City, Indonesia - nurfitri; Framita Rahman (Institut Agama Islam Negeri Palopo, 2024)
The virtue of anime is the inclusion of culture through character education that Japan wants to convey. The character education in question is the positive values conveyed such as kinship, hard work, and dreams. Anime Hotaru no haka is an anime that conveys the meaning of being full of kinship and hard work. Meanwhile, the kaze tachinu anime is an anime that conveys the meaning of always trying hard to achieve your goals. We conducted research on the effectiveness of Japanese character education as across culture for adolescents who are undergoing rehabilitation at the Baddoka Rehabilitation Center, the National Narcotics Agency, Makassar, South Sulawesi. The method used is a quantitative approach method in answering research questions. The quantitative approach used was a pre-experimental study using 1 group pretest - posttest design. The population used is adolescents who are undergoing rehabilitation, totaling 11 people, and carried out for 4 weeks. After conducting research, Japanese character education as across culture had influence on self-esteem and resilience of adolescent. Before the intervention, low self-esteem was 8 and high self-esteem was 7, but after the intervention low self-esteem decreased to 1 and high self-esteem became 14. Low resilience was 8 and high resilience 7 became low resilience 2 and high resilience 13.